Deuteronomy : a commentary - von Rad, Gerhard, 1901-1971; Barton, Dorothea M. (London, UK SCM, 1966)
Includes bibliographical references and index.
Originally published in German: Das funfte Buch Moes: Deuteronomium (Das Alte Testament Deutch 8).-- Gottingen : Vanenhoeck and Ruprecht, 1964.
Keywords: Bible. O.T. Deuteronomy -- commentaries